2023
DOI: 10.3390/ijms24098301
|View full text |Cite
|
Sign up to set email alerts
|

5-HT3 Receptors on Mitochondria Influence Mitochondrial Function

Abstract: The 5-hydroxytryptamine 3 (5-HT3) receptor belongs to the pentameric ligand-gated cation channel superfamily. Humans have five different 5-HT3 receptor subunits: A to E. The 5-HT3 receptors are located on the cell membrane, but a previous study suggested that mitochondria could also contain A subunits. In this article, we explored the distribution of 5-HT3 receptor subunits in intracellular and cell-free mitochondria. Organelle prediction software supported the localization of the A and E subunits on the inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…Removing TPH2 function during the entire reprogramming process majorly enhances the efficiency of iPSC generation, while TPH2 induction suppresses the process, indicating the importance of tryptophan pool or serotonin signaling in pluripotency acquisition (Sinenko et al, 2023). The latter possibility is supported by the observed activity of serotonin in the positive regulation of mitochondrial functions and biogenesis (Fanibunda et al, 2019;Rao et al, 2023). It has also been shown that a key enzyme in glycine degradation, glycine decarboxylase (GLDC), is involved in the early stages of cell reprogramming (Kang et al, 2019).…”
Section: Tca Cycle and Ipsc Reprogrammingmentioning
confidence: 99%
“…Removing TPH2 function during the entire reprogramming process majorly enhances the efficiency of iPSC generation, while TPH2 induction suppresses the process, indicating the importance of tryptophan pool or serotonin signaling in pluripotency acquisition (Sinenko et al, 2023). The latter possibility is supported by the observed activity of serotonin in the positive regulation of mitochondrial functions and biogenesis (Fanibunda et al, 2019;Rao et al, 2023). It has also been shown that a key enzyme in glycine degradation, glycine decarboxylase (GLDC), is involved in the early stages of cell reprogramming (Kang et al, 2019).…”
Section: Tca Cycle and Ipsc Reprogrammingmentioning
confidence: 99%